2016
DOI: 10.1159/000448245
|View full text |Cite
|
Sign up to set email alerts
|

Calciphylaxis and Martorell Hypertensive Ischemic Leg Ulcer: Same Pattern - One Pathophysiology

Abstract: This review presents a closer look at four diseases which are probably closely related to one another pathophysiologically: (a) calciphylaxis (distal pattern); (b) calciphylaxis (proximal pattern); (c) Martorell hypertensive ischemic leg ulcer; (d) calciphylaxis with normal renal and parathyroid function (synonym: eutrophication). The four diseases have largely the same risk factors: (1) arterial hypertension, (2) diabetes mellitus (types 1 and 2), (3) secondary or tertiary hyperparathyroidism (in end-stage ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 18 publications
1
54
0
11
Order By: Relevance
“…10 The shared pathophysiology of calciphylaxis, eutrophication, and HYTILU is a localized skin infarction leading to tissue necrosis. 8 Clinically, all share a similar pattern of skin infarctions and necrotizing livedo. On histopathology, all conditions have ischemia, subcutaneous arteriolosclerosis, hyperplasia of the arteriole wall musculature, and narrowed lumen diameter.…”
Section: Diagnosis Of Martorell Hytilumentioning
confidence: 99%
See 2 more Smart Citations
“…10 The shared pathophysiology of calciphylaxis, eutrophication, and HYTILU is a localized skin infarction leading to tissue necrosis. 8 Clinically, all share a similar pattern of skin infarctions and necrotizing livedo. On histopathology, all conditions have ischemia, subcutaneous arteriolosclerosis, hyperplasia of the arteriole wall musculature, and narrowed lumen diameter.…”
Section: Diagnosis Of Martorell Hytilumentioning
confidence: 99%
“…4 Both diseases present similarly as a central necrotic ulcer with an inflammatory, violaceous border; however, the wound margin is not pustular in Martorell HYTILU. 8 PG typically presents as liquefaction necrosis with a superficial moist appearance, whereas HYTILU presents as a black, dry infarction. A misdiagnosis of PG can occur due to an inadequate biopsy which may show dermal necrosis without subcutaneous arteriolosclerosis or medial calcification.…”
Section: Diagnosis Of Martorell Hytilumentioning
confidence: 99%
See 1 more Smart Citation
“…In our patient, though parathormone and calcium‐phosphate product levels were raised, we could not demonstrate calcium deposits in skin biopsy, otherwise necessary to diagnose calciphylaxis . Importantly, microvascular compromise brought on by ESRD, DM and hypertension is essentially similar and involves hyaline subcutaneous arteriolosclerosis of small arterioles and capillaries in subcutaneous fat, which occurs at the expense of lumen . Many patients do not demonstrate calcification, and it has been suggested that the luminal compromise in absence of calcification may in fact be an early stage of calciphylaxis (calciphylaxis sine calcifications) …”
mentioning
confidence: 99%
“…3 Importantly, microvascular compromise brought on by ESRD, DM and hypertension is essentially similar and involves hyaline subcutaneous arteriolosclerosis of small arterioles and capillaries in subcutaneous fat, which occurs at the expense of lumen. 4 Many patients do not demonstrate calcification, and it has been suggested that the luminal compromise in absence of calcification may in fact be an early stage of calciphylaxis (calciphylaxis sine calcifications). 5 To conclude, persistent penile ulceration can occur in setting of long-standing DM, hypertension and ESRD; and represents an atypical clinical manifestation of vascular compromise.…”
mentioning
confidence: 99%